2013
DOI: 10.1371/journal.ppat.1003709
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus Responses to Nutritional Immunity: Epigenetic and Morphological Contribution to Biofilm Architecture, Invasion, Persistence and Disease Severity

Abstract: In an effort to suppress microbial outgrowth, the host sequesters essential nutrients in a process termed nutritional immunity. However, inflammatory responses to bacterial insult can restore nutritional resources. Given that nutrient availability modulates virulence factor production and biofilm formation by other bacterial species, we hypothesized that fluctuations in heme-iron availability, particularly at privileged sites, would similarly influence Haemophilus biofilm formation and pathogenesis. Thus, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 79 publications
3
55
1
Order By: Relevance
“…We showed that Arp/2/3 plays important roles in NTHI invasion into NHBE cells. We have previously shown that the NTHI responses to nutritional immunity promote intracellular invasion and survival within host cells (113). We therefore suggest that therapeutic modulation of actin remodeling to prevent invasion will increase the vulnerability of NTHI to the host immune responses and antimicrobial therapies.…”
Section: Discussionmentioning
confidence: 89%
“…We showed that Arp/2/3 plays important roles in NTHI invasion into NHBE cells. We have previously shown that the NTHI responses to nutritional immunity promote intracellular invasion and survival within host cells (113). We therefore suggest that therapeutic modulation of actin remodeling to prevent invasion will increase the vulnerability of NTHI to the host immune responses and antimicrobial therapies.…”
Section: Discussionmentioning
confidence: 89%
“…2A). Each middle ear was individually assessed for the relative quantities of NTHI within MEF and mucosal biofilms, as is standard for this experimental model (18,19,25,26,(31)(32)(33)(34)(35)(36)(37)(38)(39). Four days after middle ear challenge with NTHI, all middle ears exhibited robust experimental OM, with high concentrations of NTHI within both MEF and mucosal biofilms ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The adherent middle ear mucosal biofilms were also collected and individually homogenized in sterile saline solution. It is well established in chinchilla models of OM that each middle ear should be considered independently (18,19,25,26,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); therefore, MEF and biofilm homogenates collected from the left and right middle ears were individually plated on chocolate agar to semiquantitatively assess the relative numbers of NTHI in the planktonic and adherent populations. MEF samples were then clarified by centrifugation, and supernatants were stored at Ϫ80°C until determination of immunoglobulin profiles as described below.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial species also depend on the host for extracting essential nutrients such as metals for their growth. For example, the Gram-negative NTHI and Gram-positive Sp require iron extracted from the serum generated by the host during inflammation(16, 17). Therefore, it is plausible that variations of these factors across hosts would lead to differences in infection kinetics between hosts.…”
Section: Variations Of Kinetics Of Polymicrobial Infectionmentioning
confidence: 99%